2017
DOI: 10.15666/aeer/1504_18831899
|View full text |Cite
|
Sign up to set email alerts
|

Protein Baits, Volatile Compounds and Irradiation Influence the Expression Profiles of Odorantbinding Protein Genes in Bactrocera Dorsalis (Diptera: Tephritidae)

Abstract: Idrees et al.: Protein baits, volatile compounds and irradiation influence the expression profiles of odorant-binding protein genes inBactrocera dorsalis Fuzhou, Fujian, 350002, *Corresponding author e-mail: jiqinge@yeah.net; phone: +86-0-59-183-789-420; fax:+86-0-59-183-789-421 (Received 4 th Jul 2017; accepted 18 th Oct 2017)Abstract. Chemical communication in insects is based on odorant-binding proteins (OBPs), but the molecular mechanisms by which these OBPs allow the perception of volatiles and host c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Therefore, many studies have focused on developing environmentally safe strategies for the management of arthropod pests [ 35 , 36 ]. Currently, biopesticides are one of the most sustainable and economical practices that could be a key component of integrated pest management [ 37 , 38 , 39 , 40 , 41 ]. A strong association has been reported between many pathogens, including viruses and fungi, with FAW [ 42 ], but only a few among them have been able to infect to the pest directly or indirectly [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many studies have focused on developing environmentally safe strategies for the management of arthropod pests [ 35 , 36 ]. Currently, biopesticides are one of the most sustainable and economical practices that could be a key component of integrated pest management [ 37 , 38 , 39 , 40 , 41 ]. A strong association has been reported between many pathogens, including viruses and fungi, with FAW [ 42 ], but only a few among them have been able to infect to the pest directly or indirectly [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, no checks and balances exist on the usage of pesticides, as some beekeepers often use acaricides such as formic acid from unknown sources while others rarely use branded soft acaricides from scientific stores. Environmentally safe options are needed to control various insect pests [18][19][20][21][22]. Different hard acaricides have been used to control this mite but have resulted in increasing mite resistance against these hard acaricides, and ultimately a reduction in their effectiveness [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that adult dietary quality, exposure to volatile compounds, and copulation impact the expression profile of OBPs and CSPs in several fruit fly species. Oriental fruit fly, B. dorsalis, exposed to attractive protein baits and volatiles from brewer’s yeast showed significantly different transcript expression profiles, and showed high expression of several OBPs including OBP2, OBP5 and OBP1 33 . Female B. tryoni mated with zingerone-fed males had different OBP expression profiles at the post-mating stage, while OBP 56a and genes encoding cuticle proteins were down regulated 32 .…”
Section: Resultsmentioning
confidence: 99%